Higher oxidative balance score is linearly associated with reduced prevalence of chronic kidney disease in individuals with metabolic syndrome: evidence from NHANES 1999–2018 - Zhu, Linying; Ruan, Xiaoyi; Wang, Jianqi; Yan, Yongxing; Tang, Chunyuan; Xu, Yuanwen (Frontiers in Nutrition, 2024)
Background: Oxidative stress is a key contributor to the development of chronic kidney disease (CKD) in individuals with metabolic syndrome (MetS). The oxidative balance score (OBS) is an emerging composite assessment tool for dietary and lifestyle oxidative balance. We aimed to explore the association of OBS with CKD prevalence in MetS in this national cross-sectional analysis. Methods: This was a national cross-sectional analysis. Eligible MetS participants ≥20 years of age from NHANES 1999-2018 were included. OBS was assessed according to previous well-validated methods and consisted of 16 dietary components and 4 lifestyle components. MetS was diagnosed by NCEP-ATP III criteria, while CKD was diagnosed by KDIGO 2021 Clinical Practice Guideline. Multivariate logistic regression models were used to explore the association of OBS with CKD in MetS in this national cross-sectional analysis. Results: A total of 8095 MetS participants were included, with a CKD prevalence of 24.8%. In fully adjusted models, each score increases in OBS, dietary OBS, and lifestyle OBS was associated with a 2%, 1.7%, and 7.3% reduction in the prevalence of CKD, respectively. Higher OBS, dietary OBS, and lifestyle OBS were all associated with significantly lower odds of CKD (p for trend all <0.05). Restricted cubic spline analysis showed that these associations all exhibited inverse dose-response. Interaction analyses indicated that cardiovascular disease (CVD) status significantly influenced the impact of OBS and dietary OBS, and these associations were only present in CVD-free subjects. Defining MetS using the IDF criteria did not significantly change the results. Conclusions: OBS was inversely associated with the prevalence of CKD in MetS, especially in CVD-free settings. These findings emphasize that adherence to an antioxidant diet and lifestyle contributes to the early prevention of CKD in the MetS population and necessitates attention to CVD interactions. Future prospective cohort studies are needed to confirm these results.